Integrating Dialectics of Quality Trilogy for Education Development in Islamic Boarding Schools - Wajdi, Muh Barid Nizarudin; Arifin, Syamsul; Haris, Abdul; Hady, M Samsul (JURNAL AL-TANZIM, 2023)
This study aims to analyze the quality pattern of education in Pondok Modern with a quality trilogy approach, namely quality planning, quality control and quality improvement. The method used in this study is descriptive qualitative phenomenological type using the Joseph M. Juran approach. This study uses interviews, observation, and documentation to collect data. In addition, this study also uses inductive modification data analysis techniques that refer to theories and concepts that emerge from the data collected. The results of the study show that Islamic boarding schools can maintain their existence by; 1) updating Islamic boarding schools education by including general and vocational subjects; 2) updating the methodology, such as the classical system and ranking; 3) institutional reform, such as pesantren leadership, diversification of educational institutions; and 3), renewal of functions, from initially only an educational function, developed so that it also includes the function of da'wah and community development in various fields. The implication of this research is to contribute to developing an educational model in Islamic boarding schools with a holistic and integrative approach that combines three essential aspects: curriculum, human resources, and relations with the community.